THE ROLE OF INFORMATION TECHNOLOGY IN THE DEVELOPMENT OF COMMUNICATIVE COMPETENCE OF STUDENTS (Web of Technology: Multidimensional Research Journal, 2024)
In the article, the role of information technology in the development of students' communicative competence is considered as an example of going through hyperlinks. Types of hyperlinks, tools to use and how to use it effectively.